Heterogeneously Integrated Membrane Lasers on Si Substrate for Low Operating Energy Optical Links - Fujii, Takuro; Takeda, Koji; Diamantopoulos, Nikolaos-Panteleimon; Kanno, Erina; Hasebe, Koichi; Nishi, Hidetaka; Nakao, Ryo; Kakitsuka, Takaaki; Matsuo, Shinji (IEEE journal of selected topics in quantum electronics, 2018)
High demand exists for low operating energy optical links that use wavelength division multiplexing technologies in datacenter networks. Thus, we fabricate a directly modulated membrane distributed-reflector laser with low operating energy on a thermally oxidized silicon (Si) substrate. Because we use epitaxial growth to bury an active region on a directly bonded InP-based membrane, it needs to be kept within a critical thickness, which is related to the growth temperature and the thermal expansion coefficients of materials. In previous studies, we used 250-nm-thick structures, causing relatively large series resistance that limited device performance on such aspects as energy cost and output power. In this study, we increase the III-V membrane thickness to 350 nm, which is close to the calculated critical thicknesses. We achieve the same high crystal quality of multiquantum-wells found in our previous studies. The fabricated laser shows a differential resistance of 72 Ω and thermal resistance of 982 K/W. Thanks to a reduction in bias voltage, the laser can be directly modulated at 25.8 Gbit/s with an energy cost of 97 fJ/bit. In addition, due to a reduction in heat generation, direct modulation with a 50-Gbit/s non return to zero signal is demonstrated by increasing bias current up to 10 mA.